Integrated Ecological and Socio-Economic Assessment for Sustainable Marine Ecotourism Development in Lihaga Island: An Ecosystem Service-Based Approach - Manembu, Indri Shelovita; Mamangkey, Noldy G.F.; Manengkey, Hermanto W.K.; Rembet, Unstain N.W.J.; Rondonuwu, Ari B. (Sam Ratulangi University, 2026)
Lihaga Island, positioned within Indonesia's Likupang Special Economic Zone, exemplifies the challenge of balancing tourism development with ecosystem conservation. This study integrates ecological and socio-economic assessments to inform sustainable management of marine ecotourism. Ecological data were collected using the Line Intercept Transect method across three stations at 3- and 10-meter depths. Results revealed a mean hard coral cover of 30.63%, which is classified as moderate according to the Indonesian Ministry of Environment Decree No. 4/2001, though significant spatial variation was observed across stations. Thirty-four coral genera were identified, dominated by Porites (36.12%). The Tourism Suitability Index scored 62%, indicating conditional suitability for diving and snorkeling. Community surveys (n=60) demonstrated overwhelming support for ecotourism (90% positive), with all respondents expressing interest in tourism village programs. However, 40% lacked tourism experience, indicating a need for capacity building. Findings reveal that sustainable development requires integrated spatial zoning, community empowerment, reef restoration, and monitoring systems. This research contributes integrated assessment frameworks for ecotourism in Indonesian Special Economic Zones and provides actionable recommendations for policymakers and stakeholders. Keywords: coral reef assessment, ecosystem services, marine ecotourism, sustainable tourism